Fluorescence and Sensing Applications of Graphene Oxide and Graphene Quantum Dots: A Review. Issue 18 (30th August 2017) - Zheng, Peng; Wu, Nianqiang
Abstract: Graphene oxide and graphene quantum dots are attractive fluorophores that are inexpensive, nontoxic, photostable, water‐soluble, biocompatible, and environmentally friendly. They find extensive applications in fluorescent biosensors and chemosensors, in which they serve as either fluorophores or quenchers. As fluorophores, they display tunable photoluminescence emission and the "giant red‐edge effect". As quenchers, they exhibit a remarkable quenching efficiency through either electron transfer or Förster resonance energy transfer (FRET) process. In this review, the origin of fluorescence and the mechanism of excitation wavelength‐dependent fluorescence of graphene oxide and graphene quantum dots are discussed. Sensor design strategies based on graphene oxide and graphene quantum dots are presented. The applications of these sensors in health care, the environment, agriculture, and food safety are highlighted. Abstract : Count on the dots ! Graphene oxide (GO; see figure) and graphene quantum dots (GQDs) have many attractive features; they are low‐cost, non‐toxic, photo‐stable, water‐soluble, biocompatible, and environmentally friendly. Most importantly, they may act as either fluorophores or quenchers in fluorescent bio‐ and chemosensors. The origin and mechanisms of this behavior and their applications as sensors in a broad range of areas of interest is discussed.